Pengaruh Independensi, Sikap Skeptisme, dan Etika Profesi Auditor terhadap Kualitas Audit: (Survei Pada Auditor Badan Pengawasan Keuangan dan Pembangunan Perwakilan Provinsi Jawa Barat) - Kholifah, Nabillah Nur; Ishak, Jouzar Farouq; Burhany, Dian Imanina; Rufaedah, Yanti (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Audit quality is a benchmark for assessing whether the state financial management of an entity being audited is good or bad. The research aims to analyze the influence of independence, scepticism and professional ethics of auditors on audit quality. Researchers use primary data by distributing questionnaires to auditors at the West Java Province Representative Financial and Development Supervisory Agency (BPKP) and secondary data taken from sources on the internet. Used probability sampling, a simple random sampling type. Researchers took a sample of 46 auditors at the BPKP Representative of West Java Province. The method used is a quantitative method with a Partial Least Square analysis tool using SmartPLS version 3.0 software. The results show independence and scepticism don't have a significant effect on audit quality, because of the characteristics of internal auditors. Auditors' characteristics can arise due to differences in external factors such as position and age. Auditor professional ethics have a significant positive effect on audit quality. Professional ethics establishes comprehensive principles to support improving audit quality. Independence, scepticism, and professional ethics of auditors simultaneously influence audit quality at the BPKP Representative of West Java Province, and the professional ethics variable has the most dominant influence on audit quality.